Osteoprotegerin-dependent M cell self-regulation balances gut infection and immunity - Shunsuke Kimura; Yutaka Nakamura; Nobuhide Kobayashi; Katsuyuki Shiroguchi; Eiryo Kawakami; Mami Mutoh; Hiromi Takahashi-Iwanaga; Takahiro Yamada; Meri Hisamoto; Midori Nakamura; Nobuyuki Udagawa; Shintaro Sato; et al. (Nature Communications, 2020)
Microfold cells (M cells) sit at the gut epithelial surface to sample antigens and maintain local immune homeostasis. Here the authors show that M cells are feedback-regulated by M cell-originated osteoprotegerin (OPG) to suppress RNAKL-induced M cell differentiation, and that OPG deficiency alters both gut colitis and infection phenotypes.